Use of oxalic acid as inducer in photocatalytic oxidation of cresol red in aqueous solution under natural and artificial light. Issue 22 (17th November 2018) - Seraghni, N.; Ghoul, I.; Lemmize, I.; Reguig, A.; Debbache, N.; Sehili, T.
ABSTRACT: This work was carried out in the field of water treatment using advanced oxidation processes (AOPs), especially photolysis of carboxylic acid that leads to the formation in situ of hydroxyl radical (·OH). Cresol red (CR) degradation induced by organic acids/UV system was investigated in aqueous solution. The preliminary study of CR-organic acid mixture in the dark and at room temperature allowed confirming the absence of interaction under our experimental conditions. However, upon irradiation at 365 nm, the proportion of elimination of CR was 89% after 5 h of irradiation. Indeed, the CR degradation efficiency depends on the acid concentration and the pH of the medium. The concentration of acid is optimized to the 5 × 10 −3 M. pH 2.39 was the optimal one when C2 HO − 4 was the most important species at this pH. The use of i-PrOH as · OH confirmed the involvement of · OH in photodegradation of CR induced by Ox. The addition of metal ions including Zn 2+ and Cu 2+ to the CR-organic acid mixture slowed the CR degradation unlike Fe 2+, hence an improvement of its disappearance was observed. The results showed a faster degradation of the pollutant under excitation by sunlight. This environmentally friendly method appears to be very effective in the treatment of wastewater.